Mobile Methodologies
XII, 193 p.
Keywords: How do we research and represent mobile experiences? This book, the first to examine mobile methods, explores the movement of bodies through space, examining perceived limitations and considering methodological responses, technologies and strategies designed to inform our understanding of people's experience of movement through space.